Czy sarna się cieli czy koci? Rozważania semantyczne = Does a roe deer calve [in polish: cieli się] or kitten [in polish: koci się]? Semantic considerations - Ruszkowski, Marek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
As it may seem, verbs denoting giving birth to offspring by various animal species have a fixed semantic connectivity, meaning that a specific verbs is uninterruptedly connected with a specific species: "a mare foals" [in Polish: źrebi się], "a bitch whelps" [in Polish: szczeni się], "a sow farrows" [in Polish: prosi się]. However, according to dictionary definitions, also a jenny ass, a zebra etc. "foals", she-wolf, vixen, female badger whelps and female wild boar "farrows". Similarly, it is not only a cow that "calves" [in Polish: cieli się], and it is not only a female cat that "kittens" [in Polish: kocić się]. That is why, this article attempts at clarifying the semantic scope of the verbs "to calve" [in Polish: cielić się] and "to kitten" [in Polish: kocić się].
Keywords: czasowniki nazywające wydawanie potomstwa; semantyka; verbs denoting giving birth to offspring; semantics